OPTIMALISASI CRM @ BRANCH SEBAGAI SALAH SATU LANGKAH MEWUJUDKAN BANK MANDIRI MENJADI THE SERVICE LEGEND - Pipin Sukandi; Heru Rizky Jiwayani (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
Based on the monitor service quality, for the second consecutive year, Mandiri Bank version of Marketing Research lndonesia (MRI) and the Bureau of Research lnfobank of